Modulating effect of DL-kavain on the mutagenicity and carcinogenicity induced by doxorubicin in Drosophila melanogaster. - Teixeira da Silva, T.; Braga Martins, J.; Do Socorro de Brito Lopes, M.; de Almeida, P.M.; Silva Sá, J.L.; Alline Martins, F. (Journal of toxicology and environmental health. Part A., 2021)
Kavain, kavalactone, present in Piper methysticum exhibits anticonvulsive, analgesic, anxiolytic, antiepileptic, antithrombotic, anti-inflammatory and antioxidant properties. Given its importance, the aim of the present study was to assess (1) the mutagenic and carcinogenicity of kavain administered alone and (2) the antimutagenic and anticarcinogenic potential when administered simultaneously with the chemotherapeutic drug doxorubicin (DXR) using the Somatic Mutation and Recombination Test (SMART) and Epithelial Tumor Test (ETT) using Drosophila melanogaster as a model system. Third-stage larvae from a standard (ST) and high metabolic bioactivation (HB) crosses were treated with different kavain concentrations (32, 64 or 128 ?g/ml), alone or in conjunction with DXR (0.125 mg/ml). In ST descendants, kavain produced no significant mutagenic or recombinogenic effects. In the HB cross, mutagenic activity was observed at kavain concentrations of 64 and 128 ?g/ml. In the DXR and kavain co-treatment, a modulating effect of the DXR-mediated mutagenic response dependent upon the concentration was detected in both crosses. In ETT, no marked carcinogenic or anticarcinogenic activity was noted for kavain. However, when kavain was combined with DXR synergistic induction of tumors by the chemotherapeutic drug occurred indicating that kavain enhanced the carcinogenic action of DXR.